SAFETY OF CAESAREAN MYOMECTOMY - Sultana, Ruqqia; Noor, Shehla; Nazar, Ali Fawwad; Abbasi, Nasreen; Bashir, Rubina; Khan, Bushra; Saleem, Faiza (Journal of Ayub Medical College Abbottabad, 2012)
Background: Uterine fibroids are the most common type of tumours in women arising from uterine myometrium and less commonly from cervix. Objective of the study was to check the safety of caesarean myomectomy. Methods: Patients attending Gynaecology-B Unit of Ayub Teaching Hospital having pregnancy with fibroid and undergoing myomectomy along with caesarean section (CS) were included in this prospective study during Jan 2010-Dec 2011. Intra-operative and postoperative maternal morbidity in terms of blood loss, operative time and length of hospital stay was compared to matched pregnant woman with caesarean section alone. Results: Out of 6,000 antenatal mothers registered during the study period myoma was detected in 96 (1.6%) cases. Mean age of mother having myoma was 28 years, 70% were primigravida, and mean haemoglobin was 10.56 gm%. Size of myoma was 12 Cm in 30% cases 5 Cm in 23% and more than 1 myoma in 60% cases. There was no significant difference in intra-operative haemorrhage and length of hospital state in comparison matched women with CS although operating time was double than later. None required caesarean hysterectomy. Conclusion: Myomectomy can be safely performed in majority of carefully selected patients with myomas without any serious life threatening complications. Keywords: Fibroids, caesarean section, myomectomy, haemorrhage